A desmosomal cadherin controls multipotent hair follicle stem cell quiescence and orchestrates regeneration through adhesion signaling - William V.J. Hariton; Katja Schulze; Siavash Rahimi; Taravat Shojaeian; Laurence Feldmeyer; Roman Schwob; Andrew M. Overmiller; Beyza S. Sayar; Luca Borradori; Mỹ G. Mahoney; Arnaud Galichet; Eliane J. Müller (iScience, 2023)
Summary: Stem cells (SCs) are critical to maintain tissue homeostasis. However, it is currently not known whether signaling through cell junctions protects quiescent epithelial SC reservoirs from depletion during disease-inflicted damage. Using the autoimmune model disease pemphigus vulgaris (PV), this study reveals an unprecedented role for a desmosomal cadherin in governing SC quiescence and regeneration through adhesion signaling in the multipotent mouse hair follicle compartment known as the bulge. Autoantibody-mediated, mechanical uncoupling of desmoglein (Dsg) 3 transadhesion activates quiescent bulge SC which lose their multipotency and stemness, become actively cycling, and finally delaminate from their epithelial niche. This then initiates a self-organized regenerative program which restores Dsg3 function and bulge morphology including SC quiescence and multipotency. These profound changes are triggered by the sole loss of functional Dsg3, resemble major signaling events in Dsg3−/− mice, and are driven by SC-relevant EGFR activation and Wnt modulation requiring longitudinal repression of Hedgehog signaling.